Efficacy of a novel veterinary argon plasma coagulation device in treating teat canal stenosis - Saat, Nevzat; Risvanli, Ali; Dogan, Halef; Safak, Tarik; Yilmaz, Oznur; Yuksel, Burak; Taskin, Mustafa (Sivar-Soc Italiana Veterinari Animali Reddito, 2023)
Teat canal stenosis is a significant factor that impedes milking and can lead to cows being unable to rear. Because the methods applied in the treatment of teat canal stenosis are mostly unsuccessful, animals with the disease are usually removed from breeding. In this case, it causes great damage to the livestock economy in the world. This study aimed to determine the efficacy of the veterinary argon plasma coagulation device, a newly developed treatment for teat canal stenosis. A two-stage study was conducted for this purpose. In the first stage, as a material, 30 teats from 30 cows of varying ages and breeds were selected. The cows were randomly divided into three groups. The first group (n=10) underwent closed operations using instruments such as occult mammary scalpels, papillomas, and udder probes, depending on the severity and condition of their teat stenosis. The second group (n=10) received a preparation containing 8 mg chemotrypsin, 8 mg trypsin, 4 mg papain, 100,000 IU retinol palmitate, and 120 mg tocopherol acetate per ml without any operation. The preparation, containing 4 mg chemotrypsin, 4 mg trypsin, and 10 mg papain in each ml, was administered intramammary three times at 12-hour intervals once a day at a dose of 0.4 ml/10 kg intramuscularly for three days. The third group (n=10) received veterinary argon plasma coagulation device through the teat canal. In the second stage, veterinary argon plasma coagulation device was utilized to treat 104 stenosed teat canals. Based on the findings, the group in which veterinary argon plasma coagulation device was applied exhibited the best recovery rate (90%) at the end of the third week in the study's first phase. In the study's second phase, 89.42% of the nipples treated with veterinary argon plasma coagulation device were completely healed. In both stages of the study, it was established that the recovery criteria could not be detected as stenosis and that the milk flow was continuous due to weekly ultrasonographic and clinical examinations. Therefore, it can be concluded that the newly developed veterinary argon plasma coagulation device is a portable device that can be used to treat teat canal stenosis.
Keywords: Veterinary; Argon; Plasma; Coagulation; teat canal; cow